The impact of corporate social responsibility on innovation in small and medium‐sized enterprises: The mediating role of debt terms and human capital - Santos‐Jaén, José Manuel; Madrid‐Guijarro, Antonia; García‐Pérez‐de‐Lema, Domingo (Corporate Social Responsibility & Environmental Management, 2021)
The aim of this paper is to study the influence of corporate social responsibility (CSR) over small and medium‐sized enterprise (SME) innovation and the effect of two mediating variables, debt terms and human capital. Based on a sample of 2825 Spanish SMEs and applying a structural equations modeling, the results demonstrate that the effect of CSR on innovation is mediated by debt terms and by good human resource practices. Part of the positive effect of CSR on innovation occurs through these two variables, which, alone, positively and significantly affect innovation in SMEs. Consequently, the positive effect of CSR practices on debt terms through a decrease in asymmetric information goes further, also having repercussions on innovation. Additionally, the suitable development of human resource practices based on strategies oriented toward CSR allow companies to carry out greater and more efficient innovative activities. This paper contributes to the CSR literature considering the human resource management and the debt access in the relationship between CSR and innovation. The findings reveal important implications for policy makers and managers. For the former, the results show that it would be interesting to carry out actions aimed at assisting SMEs, especially those with fewer resources available, to implement a suitable CSR strategy, supporting sustainable development in SMEs. And, for the latter, CSR‐oriented innovation has proven to be a valuable strategy for more efficient SMEs management because of the multiple competitive advantages it generates.
Number: 4
Keywords: Europe; Responsabilité sociétale des entreprises; Réservé UdeM